2020
DOI: 10.1186/s12916-020-1490-7
|View full text |Cite|
|
Sign up to set email alerts
|

The complex neurobiology of resilient functioning after childhood maltreatment

Abstract: Background: Childhood maltreatment has been associated with significant impairment in social, emotional and behavioural functioning later in life. Nevertheless, some individuals who have experienced childhood maltreatment function better than expected given their circumstances. Main body: Here, we provide an integrated understanding of the complex, interrelated mechanisms that facilitate such individual resilient functioning after childhood maltreatment. We aim to show that resilient functioning is not facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 211 publications
(260 reference statements)
9
136
1
4
Order By: Relevance
“…Ioannidis et al [9] further explore the effects of childhood maltreatment in an integrated overview of the neurobiological mechanisms underlying resilience. The authors embrace a systems perspective, conceptualizing resilience to adverse events in childhood as a product of a complex biopsychosocial system that includes both bottom-up (genetic and endocrinological) and top-down (social and psychological) influences.…”
Section: Mental Health and Mental Disorder As Products Of Complex Sysmentioning
confidence: 99%
“…Ioannidis et al [9] further explore the effects of childhood maltreatment in an integrated overview of the neurobiological mechanisms underlying resilience. The authors embrace a systems perspective, conceptualizing resilience to adverse events in childhood as a product of a complex biopsychosocial system that includes both bottom-up (genetic and endocrinological) and top-down (social and psychological) influences.…”
Section: Mental Health and Mental Disorder As Products Of Complex Sysmentioning
confidence: 99%
“…To this end one could for example focus on resilience predictors reviewed by Kalisch and colleagues (2015; including hair cortisol concentration, trait self-enhancement, expression of specific gene networks, and cortisol stress reactivity), 60 or on factors that predict resilient growth trajectories and resilient functioning outcomes as reviewed by Bonanno and colleagues (2011; including perceived control, high positive affectivity, low negative affectivity, trait resilience, low brooding, coping self-efficacy, emotional support, social support, instrumental support, favorable worldviews, and positive emotions), 61 or on factors that relate to resilient functioning specifically following childhood maltreatment, as reviewed in Ioannidis and colleagues (2020; including the social environment as well as biological factors related to the hypothalamic-pituitary-adrenal axis and polygenetics). 62 Overall, our results showed that the RFs were able to correctly predict the categorical ('low'/'moderate'/'high') distress class of 2 in 3 adolescents three years later. This finding was highly similar when predicting age-17 from age-14 distress.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, while this manuscript specifically focusses on using RFs that predict mental health problems (in individuals with and without CA exposure), it would be interesting to see future research taking the same modelling approach but focussing on those factors that predict a resilient functioning outcome. To this end one could for example focus on resilience predictors reviewed by Kalisch et al (including hair cortisol concentration, trait self-enhancement, expression of specific gene networks, and cortisol stress reactivity) 58 , on factors that predict resilient growth trajectories and resilient functioning outcomes as reviewed by Bonanno et al (including perceived control, high positive affectivity, low negative affectivity, trait resilience, low brooding, coping self-efficacy, emotional support, social support, instrumental support, favourable worldviews, and positive emotions) 59 , or on factors that relate to resilient functioning specifically following childhood maltreatment, as reviewed in Ioannidis et al (including the social environment as well as biological factors related to the hypothalamic-pituitary-adrenal axis and polygenetics) 60 .…”
Section: Discussionmentioning
confidence: 99%